Bioconversion of wheat bran for polygalacturonase production by Aspergillus sojae in tray type solid-state fermentation. (January 2016) - Demir, Hande; Tari, Canan
Abstract: Wheat bran was tested as the solid substrate for the tray-type solid-state fermentation (SSF) production of polygalacturonase (PG) enzyme by A. sojae mutant strain – a high-PG activity producer. PG production of A. sojae was found to reduce as the thickness of the substrate increase from 8 mm to 14 mm at 90% relative humidity. An interaction between the thickness of the bed and relative humidity of the environment was determined with the help of experimental design and statistical analysis tools. As a result, the PG activity could be enhanced by 31% as the process conditions optimized. Additionally, 11 mm thickness and 70% relative humidity were selected as the PG production favoring conditions with the maximum PG activity of 298 U/g substrate in tray type of SSF without the addition of any nutritive or inducing supplements into wheat bran. The kinetic study conducted in the trays revealed the presence of reduction in the water activity on the 4th day of the SSF process under stated conditions. The productivity of the process conducted under optimized conditions was 3.41 U/g substrate −1 h −1 for the 4th day of the SSF. Highlights: Utilization of wheat bran as substrate in tray-type SSF without any supplements. Use of tray-type SSF for the production of polygalacturonase by Aspergillus sojae . Determination of the interaction between thickness of solid bed and relative humidity. Obtaining maximum PG activity of 298 U/g substrate.